Data captured using low-cost active electromyography - Fortune, Benjamin C.; Pretty, Christopher G.; Chatfield, Logan T.; McKenzie, Lachlan R.; Hayes, Michael P. (Data in brief, 2020)
Surface electromyography (sEMG) data was captured for three able-body subjects, from their right biceps brachii using the POLE sensor outlined in “Low-cost active electromyography” [1]. Data was captured for 45 seconds per subject, resulting in 12–21 contractions per subject. The raw data files, along with a sinusoidal waveform have been provided. This allows users of the POLE sensor to verify their low-cost sEMG device has been populated and configured correctly. This data also allows researchers/developers to compare their results against this low-cost, low noise sEMG device. The frequency content of the raw sEMG data is also of interest; this is calculated by applying a fast Fourier transform (FFT). The process applied to perform these algorithms is supplied in a MATLAB script.